2017
DOI: 10.1002/lary.26795
|View full text |Cite
|
Sign up to set email alerts
|

Semicircular canal dehiscence among idiopathic intracranial hypertension patients

Abstract: 3b. Laryngoscope, 128:1196-1199, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
2
8
0
1
Order By: Relevance
“…Varios other studies reported a radiological incidence between 0,8-12% for SSCD. 7,[13][14][15][16] Our findings correlate with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…Varios other studies reported a radiological incidence between 0,8-12% for SSCD. 7,[13][14][15][16] Our findings correlate with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…The pathogenesis of SSC dehiscence has not been established 25 . Kuo et al have found no association between IIH and the presence of SSC dehiscence 26 . The stability of the bone of the SSC in the current study could be due to limitations in the study and not necessarily true absolute stability of the otic capsule.…”
Section: Discussionmentioning
confidence: 52%
“…25 Kuo et al have found no association between IIH and the presence of SSC dehiscence. 26 The stability of the bone of the SSC in the current study could be due to limitations in the study and not necessarily true absolute stability of the otic capsule. Given the retrospective nature of the study, some of the scans were of less than optimal quality for acquisition of data regarding the thickness of the bone of the SSC.…”
Section: Discussionmentioning
confidence: 82%
“…25 Whether radiographic superior semicircular canal dehiscence is more common in the setting of increased intracranial pressure remain debatable. 26 According to the prevalence of each of the diseases, the concomitant combination is calculated to be in the range of 150/100 000 of the general population, and probably much higher among revision stapes surgery candidates.…”
Section: Discussionmentioning
confidence: 99%